Virtual Collaborative Learning as One of the Effective Strategies for Raising Cross-Cultural Awareness in Business English Classroom - Tamari Dolidze; Nino Mikeladze; Anna Abesadze; Michael Jack Mansfield (European Scientific Journal, ESJ, 2024)
Recently, Business English (BE) has become an integral part of teaching English due to its growing demand in the employment market and its power to facilitate cross-cultural communication and dialogue between speakers of all languages. Since BE serves as a Lingua Franca globally, a good mastery of the so-called Business English as Lingua Franca (BELF) is getting more and more attention among practitioners and researchers of Business English, who attempt to update their curriculum by cutting-edge developments for better occupational purposes.With this in mind, the presented paper will attempt to showcase the merits of Virtual Collaborative Learning (VCL) as one of the effective strategic tools for raising cross-cultural communication in the Business English classroom which indeed fosters the development of a culturally intelligent generation through support and guidance.To assess effectiveness, a survey was conducted among students enrolled in the Business English course offered through virtual learning at Grigol Robakidze University and Azerbaijan Pedagogical University during the Spring 2021 semester. The survey included seven closed prompts using the Likert scale, ranging from "Strongly Agree" to "Strongly Disagree" and "Always" to "Never," and one open-ended question requiring a written response based on personal opinions.The responses verified the positive influence of VCL activities in promoting interaction among students from different cultures and heightened awareness of cultural understanding. The discovered insights will be integrated into the current curriculum at Grigol Robakidze University, which is scheduled for the upcoming academic year.